Application of TOPSIS Method to Design a Decision Support System in Assessing Teachers Performance - Dharmawan, Donny (Jurnal Informasi dan Teknologi, 2024)
The purpose of this project is to develop a decision support system for evaluating teacher performance based on the TOPSIS approach (a strategy that can be referred to by others based on its resemblance to an ideal solution). The investigator collected data through a variety of methods, including observations, literature reviews, online data searches, and interviewing. In the research, the author developed the system using the RAD (Rapid Application Development) paradigm. The approach is used by the author to compute teacher performance evaluations. Next, before running the code, manually simulate the TOPSIS calculations. The next step is coding, which is done using JavaScript and the PHP programming language. The web server is XAMPP, the database is MySQL, and the system creation framework is the Content Management System (CMS). The black box testing approach was employed by the author in this study. Compared to the prior duration of around one month, the black box testing approach has demonstrated the ability to complete calculations for teacher performance assessments in five minutes. Teachers with a final score above the average are considered to have good performance, while those with a score below the average indicate decreased or weak performance. Proves that from 100 teachers, there are 30 weakest teachers in the 1st criteria, 5 weakest teachers in the 13th criteria, 10 weakest teachers in the 7th criteria, 5 weakest teacher in the 10th criteria, 25 weakest teachers in the 4th criteria, and 10 weakest teachers in the 1st criteria. There are 45 weakest teachers in total, with 10 in the 11th criterion and 5 in the 12th criterion. That way, schools can follow up on each teacher's weak criteria appropriately so that they can improve teacher performance in the school.